Monetary Policy in EMU when the Transmission is Asymmetric and Uncertain - Paul De Grauwe; Marc-Alexandre Sénégas (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this paper we address the issue of how transmission uncertainty could affect the choice between a federal monetary policy based on national data and one on aggregated data.We find that the uncertainty about the transmission process increases the need to take into account information about national economies in the formulation of optimal monetary policies in a monetary union.
Keywords: 330